Prolonged Venous Transit as a Superior Predictor of Functional Outcomes in Successfully Reperfused Large Vessel Occlusions: Comparative Analysis With Cerebral Blood Volume Index and Hypoperfusion Intensity Ratio - Janet Mei; Hamza Adel Salim; Dhairya A. Lakhani; Aneri Balar; Vaibhav Vagal; Manisha Koneru; Dylan Wolman; Risheng Xu; Victor Urrutia; Elisabeth Breese Marsh; Benjamin Pulli; Meisam Hoseinyazdi; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Collateral status plays a crucial role in outcomes after acute ischemic stroke due to large vessel occlusion. Tissue‐level collaterals and venous outflow are key components following mechanical thrombectomy. This study evaluates the predictive performance of prolonged venous transit (PVT), cerebral blood volume index, and hypoperfusion intensity ratio in determining 90‐day functional outcomes. METHODS AND RESULTS We retrospectively analyzed patients with acute ischemic stroke due to large vessel occlusion with successful mechanical thrombectomy (modified Treatment in Cerebral Infarction score 2b, 2c, or 3). PVT+ was defined as Tmax ≥10 seconds in the superior sagittal sinus or torcula. Favorable hypoperfusion intensity ratio was <0.4, and cerebral blood volume index was ≥0.8. We assessed their predictive value using logistic regression and receiver operating characteristic analysis. Among 119 patients (median age: 71 years, 59.7% female), 37 (30.3%) were PVT+. Favorable 90‐day modified Rankin Scale score (≤2) was achieved in 53.8%. PVT− had a sensitivity of 84.4%, outperforming cerebral blood volume index (75.0%) and hypoperfusion intensity ratio (54.7%). Combining PVT with CBV index or hypoperfusion intensity ratio improved predictive accuracy (area under the curve: 0.716–0.727; all P<0.05). Conclusions PVT is a superior predictor of 90‐day functional outcomes compared with cerebral blood volume index and hypoperfusion intensity ratio, emphasizing the role of venous outflow in collateral assessment and stroke prognosis.